Comparison of 30-day case-fatality rate between dialysis and transplant Covid-19 patients: a propensity score matched cohort study - de Sandes-Freitas, Tainá Veras; de Andrade, Luís Gustavo Modelli [UNESP]; Moura, Lucio Roberto Requião; Cristelli, Marina Pontello; Medina-Pestana, José Osmar; Lugon, Jocemir Ronaldo; Sesso, Ricardo (Oxford University Press (OUP), 2022)
Background and objectives: Patients undergoing kidney replacement therapies (KRTs) have a poor prognosis after Covid-19 infection. Few studies have compared the outcomes of such patients in the different KRT modalities. This study aimed to analyze the 30-day Covid-19-associated case-fatality rate of dialysis and kidney transplant patients. Methods: Retrospective cohort study analyzing data from patients with confirmed Covid-19 between Mar/20 and Jan/21 included in two multicenter studies, the Brazilian Covid-19 Dialysis Study (Dialysis group, n = 703) and the Covid-19-KT Brazilian Study (Transplant group, n = 1907). To assess the risk factors for death, adjusted Cox hazards models were used. A sensitivity analysis was performed using a propensity score analysis to match the groups (n = 587 patients in each group). Results: A higher percentage of transplant patients required hospitalization (68 vs. 51%, p < 0.001), intensive care (37 vs. 30%, p = 0.023), and invasive mechanical ventilation (28 vs. 22%, p = 0.035). Multivariate analysis of the before-matching sample showed that subjects in the transplant group were at a lower death risk at baseline (HR 0.380.560.85). However, they showed higher risk over time (HR 1.031.061.09). Kaplan–Meier analysis after propensity score matching confirmed the inferior 30-day cumulative survival in the transplant recipients (83 vs. 78%, p = 0.0014). Conclusion: Both transplant and dialysis patients have high 30-day case-fatality rates after a Covid-19 diagnosis. Despite lower death risk at baseline, transplant patients have an increased death risk of 6% per day than dialysis patients. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: COVID-19; Kidney transplantation; Propensity score; Renal dialysis